2002
DOI: 10.1093/pcp/pcf020
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Photosynthetic Systems during Rewetting is Quite Rapid in a Terrestrial Cyanobacterium, Nostoc commune

Abstract: Recovery processes of photosynthetic systems during rewetting were studied in detail in a terrestrial, highly drought-tolerant cyanobacterium, Nostoc commune. With absorption of water, the weight of N. commune colony increased in three phases with half-increase times of about 1 min, 2 h and 9 h. Fluorescence intensities of phycobiliproteins and photosystem (PS) I complexes were recovered almost completely within 1 min, suggesting that their functional forms were restored very quickly. Energy transfer from allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 12 publications
7
67
0
Order By: Relevance
“…The cephalodia response to dehydration is similar to that of cyanolichens (Figs. 2 and 3) and terrestrial cyanobacteria (Satoh et al, 2002). The response observed for the green algae-containing compartments of S. sorediiferum was similar to that of previously studied chlorolichens (Kosugi et al, 2009), the aerial green alga T. aurea, and cultured Trebouxia spp.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The cephalodia response to dehydration is similar to that of cyanolichens (Figs. 2 and 3) and terrestrial cyanobacteria (Satoh et al, 2002). The response observed for the green algae-containing compartments of S. sorediiferum was similar to that of previously studied chlorolichens (Kosugi et al, 2009), the aerial green alga T. aurea, and cultured Trebouxia spp.…”
Section: Discussionsupporting
confidence: 83%
“…We recently reported a common physiological profile in desiccation-tolerant photosynthetic organisms such as N. commune (Satoh et al, 2002;Hirai et al, 2004), some bryophytes (Nabe et al, 2007), and chlorolichens (Kosugi et al, 2009). First, PSII activity is lost following the loss of photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Qian et al (1989) have reported that the recovery of photosynthesis occurs mainly during the rainy season in which the recovered photosynthesis provides compounds and energy for the growth and reproduction of N. flagelliforme. Many studies on the photosynthetic function of Nostoc commune in response to dehydration and rehydration have been performed (Hirai et al, 2004;Satoh et al, 2002), but the rate of photosynthesis recovery in N. flagelliforme was shown to be more rapid than that in N. commune (Scherer et al, 1984). Previous studies showed that the photosynthetic resumption of N. flagelliforme not only depended on light, potassium, and water (Gao et al, 1998b;Huang et al, 2005;Qiu and Gao, 1999), but also required de novo protein synthesis (Qiu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%